PECULIARITIES OF CLINICAL AND X-RAY TANGULAR FORMS OF TUBERCULOSIS AND RESULTS OF ITS ETIOLOGICAL DIAGNOSTICS IN PATIENTS CONCERNED BY HIV+TB INFECTION IN THE REPUBLIC OF KARELIA - E. V. Pahomova; Yu. M. Markelov; Т. V. Sunchalina; I. I. Rozhkova; Е. В. Пахомова; Ю. М. Маркелов; Т. В. Сунчалина; И. И. Рожкова (HIV Infection and Immunosuppressive Disorders, 2018)
The purpose of this study was to study the clinical and radiological forms of TB in patients with HIV and the possibilities of etiologic diagnosis-the detection of MBT using various methods for determining and the effect of immunosuppression on the results of etiologic diagnosis. Materials and methods. The materials for the study were the analysis of clinical x-ray examination data and the results of etiological diagnosis of the Office in the Republic of Karelia for the period from 2001 to 2016 among 159 patients with a co-infection of HIV+TB in the bacteriological laboratory of the Republican TB Dispensary of the Karelia. Results of the research. The peculiarities of clinical and radiological forms of tuberculosis (TB) and infomativity of various methods of etiologic diagnosis of TB among 159 patients with combined HIV+TB infection for the period 2001–2016 in the Republic of Karelia were studied. It was revealed that the PCR diagnostics significantly reduced the likelihood of a lethal outcome of patients with a co-infection, as it allowed us to quickly identify not only the presence of the MBT, but also to identify MDR and appoint adequate chemotherapy on the first day of detection, which significantly reduced the risk of death. The frequency of bacterial excretion most often (69%) occurred in the group of patients with the most severe immunosuppression with an amount of CD4 cells less than 100 in 1 ml. It was found that among the patients with co-infection with HIV + pulmonary TB, cavities of disintegration in the lung tissue (38,5%) are significantly less likely to be detected, but bacteriovirus (68,5%) is detected more frequently than among patients with pulmonary TB in the territory of the Republic of Karelia (form 33). It has been established that improving the organization of sputum collection can significantly increase (at least 20%) the incidence of MBT in patients with pulmonary TB and HIV, which is important in the rapid diagnosis of TB and the appointment of adequate therapy, especially considering ...